Explosive Power Level of Leg Muscles in Shooting Skills in Futsal Players - Latuheru, Ricardo Valentino (Journal of Sport Education, Coaching, and Health (JOCCA), 2024)
This descriptive correlational study aims to determine the analysis or influence of leg explosive power on shooting skills in futsal players of the Febresquard club. The population of this study was all 15 futsal players of the Febresquard club and examined all members of the population (Total Sampling). Data collection of leg explosive power used the Standing Long Jump test instrument and futsal shooting skill data used a targeted shooting test. The data was analyzed using a simple regression coefficient statistical analysis technique. From the results of the data analysis, it can be concluded as follows: There is a significant relationship/influence of leg explosive power on futsal shooting skills, with a direction coefficient (b) of 0.419 (? = 0.002) and a relationship strength of R = 0.735 (? = 0.000).